2009
DOI: 10.1371/journal.pone.0006282
|View full text |Cite
|
Sign up to set email alerts
|

Virus-Host Coevolution: Common Patterns of Nucleotide Motif Usage in Flaviviridae and Their Hosts

Abstract: Virus-host biological interaction is a continuous coevolutionary process involving both host immune system and viral escape mechanisms. Flaviviridae family is composed of fast evolving RNA viruses that infects vertebrate (mammals and birds) and/or invertebrate (ticks and mosquitoes) organisms. These host groups are very distinct life forms separated by a long evolutionary time, so lineage-specific anti-viral mechanisms are likely to have evolved. Flaviviridae viruses which infect a single host lineage would be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
209
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(226 citation statements)
references
References 91 publications
16
209
0
1
Order By: Relevance
“…This pattern is most visible in the overlapping distribution of virus clades and various Hyalomma species, consistent with a lengthy history of co-evolution of the virus with its tick vectors. A similar pattern has been observed for tick-borne flaviviruses (Lobo et al, 2009). The relative regional homogeneity of CCHFV has been demonstrated in Turkey by a systematic sampling of local isolates, which showed little genetic diversity and no evidence of ''invasion'' by strains from other regions, suggesting that the marked increase in CCHF that has occurred in Turkey over the past decade has been caused by viruses indigenous to the country (Kalaycioglu et al, 2012).…”
Section: Formation Of Discrete Genetic Lineagessupporting
confidence: 72%
“…This pattern is most visible in the overlapping distribution of virus clades and various Hyalomma species, consistent with a lengthy history of co-evolution of the virus with its tick vectors. A similar pattern has been observed for tick-borne flaviviruses (Lobo et al, 2009). The relative regional homogeneity of CCHFV has been demonstrated in Turkey by a systematic sampling of local isolates, which showed little genetic diversity and no evidence of ''invasion'' by strains from other regions, suggesting that the marked increase in CCHF that has occurred in Turkey over the past decade has been caused by viruses indigenous to the country (Kalaycioglu et al, 2012).…”
Section: Formation Of Discrete Genetic Lineagessupporting
confidence: 72%
“…Such positive association could result from immunological processes within individual mosquitoes. For example, a recent study has shown that insect-specific Flavivirus genomes are subject to similar selective pressures as those operating on the genomes of their mosquito hosts, suggesting host-virus coevolution (Lobo et al 2009). If so, then CxFV may have evolved mechanisms to reduce immune recognition by its mosquito host, which could facilitate secondary infections with similar agents such as WNV.…”
Section: Discussionmentioning
confidence: 99%
“…Krishnan et al (2008) used a human-genome-wide RNAi screen to identify 305 host proteins potentially involved in WNV infection and found a complex dependence of WNV on the host cell physiology, which required a wide variety of molecules and cellular pathways for successful infection. In addition to analyzing pathways of virus infection in hosts, examining the overall codon usage for an RNA virus open reading frame (ORF) is useful for estimating the evolutionary processes and genetic features of viruses that respond or adapt to the host cell environment (Bahir et al, 2009;Lobo et al, 2009;Wong et al, 2010;Zhou et al, 2013a,b). Recent progress has been made in measuring viral protein translation at the level of synonymous codon usage bias (Sanchez et al, 2003;Burns et al, 2006;Mueller et al, 2006;Bahir et al, 2009;Wong et al, 2010;Poyry and Jackson, 2011;Zhou et al, 2011); however, the contribution of the WNV coding sequence to replication efficiency remains unclear.…”
Section: Introductionmentioning
confidence: 99%